(untitled) (Педагогіка вищої та середньої школи, 2003)
The article is devoted to the problem of individualization of professionaloriented learning. The author considers’ the implementation technology of students’ teaching individualization as means of professional intention of foreign languages learning at non-linguistic faculties.